JUVENILE STAGES OF A FILE-FISH ASSIGNED TO PARAMONACANTHUS CHOIROCEPHALVS (BLEEKER) - Pillai, P K Mahadevan (Indian Journal of Fisheries, 2011)
A brief description of two juvenile stages of a file-flsh is given. A close study oftheir fin ray counts and the arrangement of spinnules on the dorsal spine revealed theirnearness to Paramonacanthus choirocephalus (Bleeker). Similarities exhibited by thesespjcimens to other allied species are discussed.